Valuation, Adverse Selection, and Market Collapses - Fishman, Michael J.; Parker, Jonathan A. (Review of Financial Studies, 2015)
We study a market for funding real investment where valuation—meaning investors devoting resources to acquiring information about future payoffs—creates an adverse selection problem. Unlike previous models, more valuation is associated with lower market prices and so greater returns to valuation. This strategic complementarity in the capacity to do valuation generates multiple equilibria. With multiple equilibria, the equilibrium without valuation is most efficient despite funding some unprofitable investments. Switches to valuation equilibria, valuation runs, look like credit crunches. A large investor can ensure the efficient equilibrium only if it can precommit to a price and potentially, only if subsidized.